2014
DOI: 10.1016/j.bmcl.2014.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Substituted piperidines as HDM2 inhibitors

Abstract: Novel small molecule HDM2 inhibitor, substituted piperidine, was identified. Initial SAR study indicated potential for several position optimizations. Additional potency enhancement was achieved by introducing a sidechain off the aromatic ring. DMPK study of one of the active compounds has shown a moderate oral PK and reasonable bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The substituted piperidines 14a and 14b were identified as hits with micromolar potency by a screening campaign at Merck using a MDM2-p53 fluorescence polarization assay (Figure 7) [32]. Optimization of the piperazine amide moiety showed that replacement of the pyridine nitrogen with an alkoxy substituent gave improved potency, and the 2-methoxyethoxy substituent was taken into the next round of SAR (14c, Table 6).…”
Section: Rg7388 Seriesmentioning
confidence: 99%
“…The substituted piperidines 14a and 14b were identified as hits with micromolar potency by a screening campaign at Merck using a MDM2-p53 fluorescence polarization assay (Figure 7) [32]. Optimization of the piperazine amide moiety showed that replacement of the pyridine nitrogen with an alkoxy substituent gave improved potency, and the 2-methoxyethoxy substituent was taken into the next round of SAR (14c, Table 6).…”
Section: Rg7388 Seriesmentioning
confidence: 99%
“…Merck scientists have reported a class of piperidine-containing compounds as MDM2 inhibitors with IC 50 values as low as 41 nM [73]. Novartis has explored several small molecular scaffolds such as 3-imidazolylindoles, substituted dihydroimidazole derivatives, tetrasubstituted heteroaryl compounds, and substituted isoquinolinones and quinazolinones as inhibitors of MDM2 and/or MDMX [74].…”
Section: Small Molecules As Inhibitors Of Mdm2-p5interactionmentioning
confidence: 99%
“…As described earlier, 20,23,24 the team capitalized on the Bargellini reaction of protected 3-piperidinone 26a and 26b with various alcohol moieties to assemble in one-pot the gemdisubstituted piperidine core of type 27a and 27b. 20 Efficient acid chloride coupling procedures were developed to install 4-(trifluoromethyl)-nicotinic acid 28 as well as 1-(2-alkoxyphenyl)piperazine hydrochloride of type 32 into final targets. Another synthetic approach relied on standard HATU coupling procedures, installing first 1-(2-alkoxyphenyl)-piperazine moieties 32 then 4-(trifluoromethyl)-nicotinic acid 28 to deliver compounds of type 34.…”
Section: * S Supporting Informationmentioning
confidence: 99%